Beliefs about mathematics and achievement among Kosovar students - Ukaj, Lekë (Sodobna pedagogika, 2025)
This study examines the mediating roles of curiosity and mathematics anxiety in the relationship between students’ beliefs about mathematics and their mathematics achievement using structural equation modelling analysis. A quantitative research design was adopted, and the data were analysed using Mplus and IBM SPSS. The representative sample comprised 6,027 Kosovar students drawn from the PISA 2022 database. The dependent variable was the mathematics scores earned by Kosovar students in PISA 2022. The independent variables include the items from the PISA 2022 Student Questionnaire: ‘beliefs about mathematics’ and the mediators ‘curiosity’ and ‘anxiety’. The results revealed that strong beliefs about mathematics positively influence achievement, and curiosity also has a positive effect, whereas mathematics anxiety negatively affects achievement. Furthermore, both curiosity and anxiety mediate the relationship between beliefs about mathematics and mathematics achievement.
Keywords: anxiety; dosežki pri matematiki; learning difficulties; mathematics achivement; mathematics lessons; pedagogy; pedgogika; PISA 2022; pouk matematike; tesnoba; učne težave